Determinants Of Saving Interest In Islamic Banks: The Role Of Religiosity, Accessibility, And Income In Sumberagung Village - Kerishna Mukti Wibowo; Nihayatu Aslamatis Solekah (UNIVED Press, 2026)
This study aims to determine the influence of religiosity, accessibility, and income level on the saving interest in Islamic banks among the community of Sumberagung Village, Gandusari District, Blitar Regency. This research uses a quantitative method with 98 respondents from the village as the research subjects. The sampling technique used was purposive sampling. Data analysis was conducted using multiple linear regression analysis with the help of IBM SPSS Statistics version 26 software. The variables studied were religiosity (X1), accessibility (X2), income level (X3), and the saving interest in Islamic banks among the village community (Y). The results showed that religiosity, accessibility, and income level significantly influence the saving interest of the village community in Islamic banks. The finding of this study indicates that the accessibility variable has a greater value compared to religiosity and income level, which means that accessibility has a more dominant influence on the saving interest of the village community in Islamic banks. The implication of this result is the importance of improving the accessibility of the community to Islamic banking services, both in terms of location, infrastructure, and the availability of supporting information and technology.